Spatial pattern of plutonium and radiocaesium contamination released during the Fukushima Daiichi nuclear power plant disaster. Issue 1 (December 2018) - Dunne, James; Martin, Peter; Yamashiki, Yosuke; Ang, Ian; Scott, Tom; Richards, David
Abstract Plutonium and radiocaesium are hazardous contaminants released by the Fukushima Daiichi nuclear power plant (FDNPP) disaster and their distribution in the environment requires careful characterisation using isotopic information. Comprehensive spatial survey of134 Cs and137 Cs has been conducted on a regular basis since the accident, but the dataset for135 Cs/137 Cs atom ratios and trace isotopic analysis of Pu remains limited because of analytical challenges. We have developed a combined chemical procedure to separate Pu and Cs for isotopic analysis of environmental samples from contaminated catchments. Ultra-trace analyses reveal a FDNPP Pu signature in environmental samples, some from further afield than previously reported. For two samples, we attribute the dominant source of Pu to Reactor Unit 3. We review the mechanisms responsible for an emergent spatial pattern in134, 135 Cs/137 Cs in areas northwest (high134 Cs/137 Cs, low135 Cs/137 Cs) and southwest (low134 Cs/137 Cs, high135 Cs/137 Cs) of FDNPP. Several samples exhibit consistent134, 135 Cs/137 Cs values that are significantly different from those deposited on plant specimens collected in previous works. A complex spatial pattern of Pu and Cs isotopic signature is apparent. To confidently attribute the sources of mixed fallout material, future studies must focus on analysis of individual FDNPP-derived particles.